Potential multifunctional agents with anti-hepatoma and anti-inflammation properties by inhibiting NF-кB activation - Chang-Ming Su; Gui-Ge Hou; Chun-Hua Wang; Hong-Qin Zhang; Cheng Yang; Mei Liu; Yun Hou (Taylor & Francis Group, 2019)
Inhibition of NF-κB signalling has been demonstrated as a therapeutic option in treating inflammatory diseases and cancers. Herein, we synthesized novel dissymmetric 3,5-bis(arylidene)-4-piperidones (BAPs, 83-102) and characterized fully. MTT and ELISA assay were performed to screen the anti-hepatoma and anti-inflammation properties. 96 showed the most potential bioactivity. 96 could promote HepG2 apoptosis through up-regulating the expression of C-Caspase-3 and Bax, down-regulating the expression of Bcl-2, while markedly inhibit LPS or TNF-α-induced activation of NF-κB through both inhibiting the phosphorylation of IκBα and p65, and preventing the p65 nuclear translocation to exhibit both anti-hepatoma and anti-inflammatory activities. Molecular docking verified that simulated 96 can effectively bond to the active site of Bcl-2 and NF-κB/p65 proteins. 96 inhibited xenografts growth by reducing the expression of TNF-α and Bcl-2 in the tumour tissue. This study suggested that 96 could be developed as a potential multifunctional agent for treatment of inflammatory diseases and cancers.